Prestatus and status dystonicus in children and adolescents. (13th December 2019) - Garone, Giacomo; Graziola, Federica; Nicita, Francesco; Frascarelli, Flaminia; Randi, Franco; Zazza, Marco; Cantonetti, Laura; Cossu, Silvia; Marras, Carlo Efisio; Capuano, Alessandro
Abstract : Aim: To critically analyse the management of status dystonicus and prestatus dystonicus in children and adolescents, in order to examine clinical features, acute management, and risk of relapse in a paediatric cohort. Method: Clinical, demographic, and therapeutic features were analysed according to disease severity. Risk of subsequent relapse was estimated through Kaplan–Meier curves. Results: Thirty‐four patients (eight females, 26 males) experiencing 63 episodes of acute dystonia exacerbations at a tertiary referral Italian hospital were identified. Mean age at status dystonicus presentation was 9 years 11 months (11y at inclusion in the study). Onset of dystonia dated back to infancy in most cases. Fourteen patients experienced two or more episodes. Infections were the most common trigger (48%). Benzodiazepines were the most commonly used drugs for acute management. Stereotactic pallidotomy was performed in six cases during status dystonicus, and in two additional patients it was electively performed after medical management. The probability of survival free from status dystonicus relapses was 78% after 4 months and 61% after 27 months. Interpretation: Dystonia exacerbations are potentially life‐threating emergencies, with a considerable risk of relapse. Nevertheless, no obvious factors for relapse risk stratification exist. Pallidotomy is a feasible option in medical refractory status dystonicus for patients with limited deep brain stimulation applicability, but the risk of recurrence is elevated. What this paper adds: Acute exacerbations may affect up to 10% of children with dystonia. Infections are the most common precipitant factor. In about 30% of the cases, intensive care unit admission is needed. Subsequent relapses are common, reaching 25% risk at 1 year. Pallidotomy can be considered in medical‐refractory cases with no deep brain stimulation applicability. What this paper adds: Acute exacerbations may affect up to 10% of children with dystonia. Infections are the most common precipitant factor. In about 30% of the cases, intensive care unit admission is needed. Subsequent relapses are common, reaching 25% risk at 1 year. Pallidotomy can be considered in medical‐refractory cases with no deep brain stimulation applicability. Video Podcast: https://www.youtube.com/watch?v=CQ30o-UDjDg&feature=youtu.be This article is commented on by Lumsden on page 668 of this issue.